2023
DOI: 10.3389/fimmu.2023.1093514
|View full text |Cite
|
Sign up to set email alerts
|

The association between genetic variants at 3’-UTR and 5’-URR of HLA-G gene and the clinical outcomes of patients with leukemia receiving hematopoietic stem cell transplantation

Abstract: In addition to the classical human leukocyte antigen (HLA) genes, the outcomes of post-hematopoietic stem cell transplantation (HSCT) are associated with human leukocyte antigen (HLA)-related genes and non-HLA genes involved in immune regulation. HLA-G gene plays an important role in immune tolerance, assisting immune escape of tumor cells, and decrease of transplant rejection. In this study, we explored the association of genetic variants at the 3’-untranslated region (3’-UTR) and 5’-upstream regulatory regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…28,29 For example, SNPs in the regulatory region of HLA-G gene were found relative to cancers. [14][15][16] However, whether the SNP in regulatory region of HLA-E gene is associated with diseases, it remains unclear. In our study, we found the correlation between rs76971248 SNP in the regulatory region and myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28,29 For example, SNPs in the regulatory region of HLA-G gene were found relative to cancers. [14][15][16] However, whether the SNP in regulatory region of HLA-E gene is associated with diseases, it remains unclear. In our study, we found the correlation between rs76971248 SNP in the regulatory region and myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the SNPs in regulatory region of HLA‐E gene among healthy individuals 28,29 . For example, SNPs in the regulatory region of HLA‐G gene were found relative to cancers 14–16 . However, whether the SNP in regulatory region of HLA‐E gene is associated with diseases, it remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic polymorphisms in the 3'-untranslated region (UTR) of HLA-G have been linked to posttranscriptional alteration of HLA-G expression and a wide range of clinical complications, including autoimmunity, chronic in ammation, viral infections, allografting, and cancer (Chen et al 2023). Harmful effects that HLA-G triggers include immunological escape mechanisms, while it positively in uences innate and adaptive immune responses and tolerance development (Jasinski-Bergner, Eckstein, et al…”
Section: Introductionmentioning
confidence: 99%